Research of Single-phase Grounding Fault Location of Underground 10 kV Distribution Network - LI Pan; YUN Bao-ji; FAN Xiao-ming (Gong-kuang zidonghua, 2012)
In view of problems that measured fault current of power frequency by existing fault location methods is weak and electric arc is unstable, a new fault location method based on parameter identification was put forward. The method uses lumped parameter Γ model to established fault point location time domain equations of single phase grounding fault, and uses transient time domain information to identify fault point position through the least squares optimization algorithm. EMTP simulation results validated accuracy of the method under different fault conditions.